Visual scripting approach for structural safety assessment of masonry walls - Lasorella Mariaceleste; Percolla Giulia; Pisano Aurora Angela; Fuschi Paolo (Curved and Layered Structures)
A visual scripting approach for limit analysis of masonry walls subjected to out-of-plane loads is proposed. To this aim, within a visual scripting framework, an interactive CAD representation of the structure and of the acting loads, boundary conditions, and restraints is coupled with an optimization algorithm to calculate the collapse load multiplier and visualize the related predicted collapse mechanism. The proposed approach can be useful for practical purposes, indeed it allows us to quickly identify the key factors that influence the structural response and, through the tuning of some input data, can furnish some hints for design purposes. The effectiveness of the promoted tool is verified by application to eight well-known benchmark cases.